The effect of education, training, and work experience on the employment probability of people with disabilities in Indonesia - Labibah, Salma; Handayani, Dwini (Journal of Gender Equality Disability Social Inclusion and Children, 2026)
Background: The significant gap in labor force participation among Indonesia's 22.5 million persons with disabilities poses an urgent challenge to inclusive development, despite the existence of affirmative policy frameworks. This study aims to analyze the influence of human capital, measured by education level, training, and work experience, on the probability of employment among persons with disabilities. Methods: This study uses a mixed-methods approach, processing quantitative data from the February 2024 National Labor Force Survey (Sakernas) with a logistic regression (logit) model and reinforced with qualitative analysis through in-depth interviews. Findings: The results of the study show that higher education and participation in job training significantly increase the probability of employment for people with disabilities. However, this study reveals a crucial contrasting finding: secondary education has no significant effect, while work experience and residence on the island of Java are negatively correlated with employment opportunities. Qualitative interviews explain this paradox, in which systemic discrimination, stigma, and structural barriers in the workplace effectively negate the benefits of human capital. Conclusion: Investment in human capital (supply side) is important but insufficient if not balanced with intervention on the demand side. The main barriers to the inclusion of persons with disabilities in the workforce lie in discriminatory practices by employers and the lack of an accommodative work environment. Therefore, policy recommendations must shift from merely training individuals to strict law enforcement, incentives for proper accommodation, and changes in corporate culture to create a truly inclusive job market. Novelty/Originality of this article: This study uniquely combines recent Sakernas 2024 data and mixed methods to reveal how discrimination and structural barriers undermine human capital returns for persons with disabilities in Indonesia.